Application of hybrid III-V on silicon lasers to near-infrared spectroscopy - Thakor, Meetsinh (2024)
Silicon photonics (SiPh) is a rapidly evolving technology that takes advantage of silicon as an optical medium to create highly integrated and scalable photonic circuits for a wide range of applications. A variety of optical functions have been successfully implemented on this platform, leading to the development of complex and powerful Photonics Integrated Circuits (PICs). However, the integration of laser sources is still not fully developed, which hampers any further cost reduction for silicon photonic systems-on-chip and limits the expansion of this platform to more diverse applications. Making non-invasive continuous glucose monitoring (CGM) devices has been quite popular from the last decade but still haven’t developed a device which is highly accurate, cheap and has a longer life span. This thesis is part of a big project for aiming a cheap CGM and gas sensing device based on photoacoustic spectroscopy (PAS). Here, we discuss a promising technology of making an on-chip laser source via the microtransfer-printing (μTP) technique, which is currently in its earlier phase for adding IIIV-based material on passive Si wafers. This on-chip laser source was designed under the internal development project of IMEC, and the fabrication of a 200 mm PIC wafer was done under IMEC’s cleanroom facility and μTP was done in Ghent. The thesis aimed to characterize the tunable lasers and their maximum modulation capability. Each laser die chip has multiple laser sources (called bank of lasers) and gives combined edge output in the range of 1400nm to 1700nm. The purpose of these lasers is to be used for PAS experiments and aim towards taking PAS out from the laboratory to real-life applications via making compact sensing devices for commercial uses. These laser sources are in the telecom band and have initial uses for detecting gas and glucose sensing. The project design has included many lasers for sensing purposes, we only see here two laser designs separated based on their waveguide material, an amorphous silicon (a-Si) based, and a second Silicon-nitride (SiN) based. This thesis includes understanding tunable on-chip lasers, as well as Vernier rings, phase shifters and Sagnac loop mirrors. The procedure includes cold cavity measurement and analysis of wafers which showed the second and third cavities are best for the narrowest output laser line width, the PCB designs task for each type of laser source which supports edge coupling laser output, further in chip processing and packaging the chip dicing, removing photoresistor, microscopic analysis of chips, electrical characterization of laser and wire bonding. For the laser characterization, discussing the experiment setup design, the result of nearly 70 nm tunning via both ranges of single laser source, and laser modulation was also allowed to sine and square wave for limit in several KHz.